Coastal population vulnerability to sea level rise and tropical cyclone intensification under global warming - Barnes, Celeste C. (Lethbridge, Alta. : University of Lethbridge, Dept. of Geography, 2014, 2014)
This research focuses on developing a framework for first order estimates of locations at risk to Tropical Cyclones (TC) and elevated water levels in coastal regions. The International Best Track Archive for Climate Stewardship (IBTrACS) 64 knot wind radii data identifies locations in the North Atlantic (NA) basin hit by hurricane strength storms. Geographic Information System (GIS) temporal and spatial analysis of IBTrACS data identifies impact zone locations where multiple TCs have occurred. Aster 30 m elevation data identifies locations within 5 and 10 m of sea level that may become inundated by TC storm surges. Population density and land cover data maps are created to identify urban and food production areas. Overlay maps are created of the coastal inundations, population, land cover, and hurricane track impact zones. Mapping results show the Bahamas and Cuba are most susceptible to the effects of tropical cyclone and storm surge inundation.